تاثير استخدام التعلم المتنقل في تعلم السباحة الحرة وتنمية الاتجاهات نحوها - سلمان, جنان; اسماعيل, هويدا (Sulaimani Journal for Humanities, 2018)
Recently a modern technologies, was emerged and spread rapidly in all countries, And also in Iraq the mobile phone, which has become a present for most of the members of society and Because swimming is difficult skills whish few females used it, that reflects on the level of learning and attitudes of learners towards it . it was necessary for researchers to pause for the purpose of considering the possibility to take advantage of this technique as a belief researchers that it may contribute to the upgrading of the educational process on the way out of the restrictions time and place of a wall in the halls and lectures to the wider world whish hs more enjoyable Therefore they could improve the process of learning swimming and attitudes towards it, so the goals of research is to get to know students trends towards free swimming and then identify the impact of the use of mobile learning in learning and attitudes it